Challenges of religion and music in contemporary Iran (1971-2018); A historical research - H. Sarvi; H. Mohaddesi Gilvaei; R. Samim (Taḥqīqāt-i Farhangī-i Īrān)
This paper discusses the government's view on contemporary Iranian music as well as the relationship between religion and art during the years 1971 to 2018. Thus, the relationship between the two institutions of religion and art was examined through sociological perspectives. For that matter, qualitative and analytical approaches were applied, with the first relying on historical method where the tool was historical documents (newspapers) and oral history (interviews with elites) and the second analyzing the statistics published by the Music Division of the Ministry of Culture and Islamic Guidance. In terms of data type, this is a historical research. The required data include three categories published by national press between 1971 and 2018, data related to interviewees and those published by the Music Division of the Ministry of Culture and Islamic Guidance from 1982 to 2018. The results showed that the media information, interviews and the Music Bureau data are in one direction with regard to the state of music between 1971 and 2018 in a way that music was completely weakened in the 1980s due to the dominance of religious view on the country. The present study, by examining three data groups, showed the stage of challenges the two institutions of religion and art have faced in contemporary Iran. These challenges have, sometimes, led to severe stances of active and effective forces in these two social institutions against each other. However, artistic forces are gradually in the process to free themselves from the domination of religious institutions and gain independence.